The Status of Screening Tests for Women\'s Common Cancers in the Personnel of the Educational-Medical and Health Centers - Massoomeh Amani; Seyedeh Noshaz Mirhaghjou; Maryam Niknami; Ehsan Kazem Nezhad Leyli (Journal of Holistic Nursing and Midwifery)
Introduction: Among women s cancers, breast and cervical cancers are most common with high mortality rate, but they can be rectified in the initial stages with cost-effective, easy and readily available screening programs. The task of informing the community and directing them towards the screening programs is one of the major responsibilities of the health team. Objective: Determining the screening test status for common female cancers and their associated factors among the personnel working in the health and educational centers. Materials and Methods: In this cross-sectional and analytical study, 212 employees (physicians, gynecologists, nurses, midwives and family health unit personnel) from Al-Zahra Medical Center and the health centers of Rasht City (15 centers) were studied. A 4-part questionnaire was prepared and completed by the selected employees. For statistical analysis, descriptive characteristics and Independent t test were used. To determine the predictor-related factors for conducting Pap Smear test, mammography and breast self-examination, multiple analysis and logistic regression model were used. Results: The results showed that 76.80% of the subjects with regard to Pap Smear test, 50% with regard to mammography and 86.60% with regard to breast self-examination had a good performance. Age (B=-0.12, P=0.007), age of the first pregnancy (B=0.14, P=0.05) and early diagnosis of cancer by screening (B=1.21, P=0.04) were predictive factors for performing Pap Smear. Duration of the current contraceptive method (P=0.05, B=-0.07), presence of suspicious mass in the breast (B=2.095, P=0.004) and fear of cancer (B=-0.85, P=0.07) were predictive factors for performing mammography. While, fear of cancer (P=0.02, B=6.31) was the only predictor of breast self-examination. Conclusion: Considering that working personnel in health-care centers are models for the general public, promoting their health behaviors such as performing timely tests can be an effective approach to promote better health in the community.